Baicalin Attenuated Aβ1-42-Induced Apoptosis in SH-SY5Y Cells by Inhibiting the Ras-ERK Signaling Pathway. (27th April 2022) - Song, Zhenyan; He, Chunxiang; Yu, Wenjing; Yang, Miao; Li, Ze; Li, Ping; Zhu, Xu; Xiao, Chen; Cheng, Shaowu
Abstract : Alzheimer's disease (AD) is a serious neurodegenerative disease. It is widely believed that the accumulation of amyloid beta (A β ) in neurons around neurofibrillary plaques is the main pathological characteristic of AD; however, the molecular mechanism underlying these pathological changes is not clear. Baicalin is a flavonoid extracted from the dry root of Scutellaria baicalensis Georgi . Studies have shown that baicalin exerts excellent anti-inflammatory and neuroprotective effects. In this study, an AD cell model was established by exposing SH-SY5Y cells to A β 1-42 and treating them with baicalin. Cell survival, cell cycle progression, and apoptosis were measured by MTT, flow cytometry, and immunofluorescence assays, respectively. The expression levels of Ras, ERK/ERK phosphorylation (p-ERK), and cyclin D1 were measured by Western blotting. In addition, whether the MEK activator could reverse the regulatory effect of baicalin on Ras-ERK signaling was investigated using Western blotting. We found that baicalin improved the survival, promoted the proliferation, and inhibited the apoptosis of SH-SY5Y cells after A β 1-42 treatment. Baicalin also ameliorated A β 1-42 -induced cell cycle arrest at the S phase and induced apoptosis. Furthermore, baicalin inhibited the levels of Ras, p-ERK, and cyclin D1 induced by A β, and this effect could be reversed by the MEK activator. Therefore, we suggest that baicalin may regulate neuronal cell cycle progression and apoptosis in A β 1-42 -treated SH-SY5Y cells by inhibiting the Ras-ERK signaling pathway. This study suggested that baicalin might be a useful therapeutic agent for senile dementia, especially AD.